ПРОСТРАНСТВЕННЫЙ ГАРМОНИЧЕСКИЙ АНАЛИЗ МАГНИТНОГО ПОЛЯ ДАТЧИКА ПЛАЗМЫ КОСМИЧЕСКОГО АППАРАТА - Гетьман, А.В. (Інститут електродинаміки НАН України, Київ, 2013)
The spatial harmonics analysis of the magnetic field, what created by the magnetized part of the sensor of the neutral component of the plasma from the scientific instruments of the spacecraft "Mikrosat”, was performed. Based on this analysis, produced the assessment magnetic noise by the sensor in the area onboard magnetometer. References 6, figures 4.